DINAR-DIRHAM SEBAGAI ETIKA MONETER: IMPLIKASI AL-QUR’AN BAGI KEADILAN FINANSIAL DI ERA DIGITAL - Aang Kunaifi; Darwis (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2026)
The modern global monetary system based on fiat currency has generated significant structural problems, particularly for developing nations and most Muslim-majority countries. Fiat money, which lacks intrinsic value, creates exchange-rate volatility, chronic inflation, and deep dependence on the United States dollar. This study examines these issues through the lens of Qur’anic interpretation, focusing on the references to dinar and dirham as monetary instruments rooted in precious metals. An analysis of relevant Qur’anic verses, especially Surah Al-Imran (3:75) and At-Taubah (9:34), demonstrates the theological legitimacy of gold and silver as stable, just, and non-manipulable measures of value. The research also presents empirical evidence from Indonesia, Egypt, Turkey, Lebanon, Pakistan, Libya, and Saudi Arabia, all of which have experienced major monetary crises over the past century, including hyperinflation, banking collapses, and severe loss of purchasing power under fiat systems. Conversely, gold and silver have maintained long-term stability without structural depreciation. The findings highlight the urgent need to reconstruct Islamic monetary thought and reaffirm the relevance of restoring the dinar and dirham as the foundation of a fair, stable, and sustainable economic system for Muslim nations in the modern era